A 2-Year Prospective Cohort Study of Overuse Running Injuries: The Runners and Injury Longitudinal Study (TRAILS). Issue 9 (July 2018) - Messier, Stephen P.; Martin, David F.; Mihalko, Shannon L.; Ip, Edward; DeVita, Paul; Cannon, D. Wayne; Love, Monica; Beringer, Danielle; Saldana, Santiago; Fellin, Rebecca E.; Seay, Joseph F.
Background: The National Center for Injury Prevention and Control, noting flaws in previous running injury research, called for more rigorous prospective designs and comprehensive analyses to define the origin of running injuries. Purpose: To determine the risk factors that differentiate recreational runners who remain uninjured from those diagnosed with an overuse running injury during a 2-year observational period. Study Design: Cohort study; Level of evidence, 2. Methods: Inclusion criteria were running a minimum of 5 miles per week and being injury free for at least the past 6 months. Data were collected at baseline on training, medical and injury histories, demographics, anthropometrics, strength, gait biomechanics, and psychosocial variables. Injuries occurring over the 2-year observation period were diagnosed by an orthopaedic surgeon on the basis of predetermined definitions. Results: Of the 300 runners who entered the study, 199 (66%) sustained at least 1 injury, including 73% of women and 62% of men. Of the injured runners, 111 (56%) sustained injuries more than once. In bivariate analyses, significant ( P ≤ .05) factors at baseline that predicted injury were as follows: Short Form Health Survey–12 mental component score (lower mental health–related quality of life), Positive and Negative Affect Scale negative affect score (more negative emotions), sex (higher percentage of women were injured), and knee stiffness (greater stiffness was associated with injury); subsequently, knee stiffness was the lone significant predictor of injury (odds ratio = 1.18) in a multivariable analysis. Flexibility, quadriceps angle, arch height, rearfoot motion, strength, footwear, and previous injury were not significant risk factors for injury. Conclusion: The results of this study indicate the following: (1) among recreational runners, women sustain injuries at a higher rate than men; (2) greater knee stiffness, more common in runners with higher body weights (≥80 kg), significantly increases the odds of sustaining an overuse running injury; and (3) contrary to several long-held beliefs, flexibility, arch height, quadriceps angle, rearfoot motion, lower extremity strength, weekly mileage, footwear, and previous injury are not significant etiologic factors across all overuse running injuries.